Manajemen Pembelajaran Full Day School Berbasis Pendidikan Karakter - Wahyunita Rahmawati; Imron Arifin; Sultoni Sultoni; Wahyunita Rahmawati; Imron Arifin (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: The purpose of this research is to describe (1) planning, (2) organizing, (3) implementation, and (4) evaluation of instructional based on character education at full day school. This research uses qualitative approach with case study type. Technique of collecting data is done by interview, observation, and documentation. Then the test of data validity include credibility, dependability, and confirmability. The results of the study are: (1) instructional planning includes making the indicator by the school in accordance with K13 PAUD and the determination of theme/sub theme/topic according to vision, mission, and school objectives; selection of indicators according to the theme and center (semester program); make RPPM; make RPPH; socialization to student guardians; and APE preparation; Characters that want to be upgraded by the school that is optimistic, responsible, akhlakul karimah, increase creativity, and enthusiasm (2) instructional organizing include division of tasks, job description, schedule center, coordination schedule, and schedule of daily activities; (3) instructional implementation includes opening, core and closing activities; (4) instructional evaluation is done everyday and recapitulated every week. Then the form of daily reports in the form of liaison books and semester reports in the form of report cards. Then for the character reports in general made by the psychological coordinator in the form of psychological records. Abstrak: Tujuan penelitian ini yaitu untuk mendeskripsikan (1) perencanaan, (2) pengorganisasian, (3) pelaksanaan, dan (4) pengevaluasian pembelajaran full day school berbasis pendidikan karakter. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Teknik pengumpulan data dilakukan dengan wawancara, observasi, dan dokumentasi. Kemudian uji keabsahan data meliputi kredibilitas, dependabilitas, dan konfirmabilitas. Hasil penelitian adalah: (1) perencanaan pembelajaran meliputi pembuatan indikator oleh sekolah sesuai dengan K13 PAUD dan penentuan tema/sub tema/topik sesuai dengan visi, misi, dan tujuan sekolah; pemilihan indikator sesuai dengan tema dan sentra (program semester); membuat RPPM; membuat RPPH; sosialisasi kepada walimurid; dan penyiapan APE; Karakter yang ingin ditingkatkan oleh sekolah yaitu optimis, bertanggung jawab, akhlakul karimah, meningkatkan kreativitas,dan antusias (2) pengorganisasian pembelajaran meliputi pembagian tugas, job description, jadwal sentra, jadwal koordinasi, dan jadwal kegiatan harian; (3) pelaksanaan pembelajaran meliputi kegiatan pembukaan, inti, dan penutup; (4) pengevaluasian pembelajaran dilakukan setiap hari dan direkap setiap minggu. Kemudian bentuk laporan harian berupa buku penghubung dan laporan semester berupa raport. Kemudian untuk laporan karakter secara umum yang dibuat oleh koordinator psikologi berupa catatan psikologis.